2022
DOI: 10.1021/acsami.1c24008
|View full text |Cite
|
Sign up to set email alerts
|

Specific Ion Effects in Lanthanide–Amphiphile Structures at the Air–Water Interface and Their Implications for Selective Separation

Abstract: The use of surfactants to attract dissolved ions to water surfaces and interfaces is an essential step in both solvent-based and solvent-free separation processes. We have studied the interactions of lanthanide ions in the aqueous subphase with monolayers of dihexadecyl phosphate at air–water interfaces. With heavier lanthanides (atomic number Z ≥ 65) in the subphase, the floating layer can be compressed to an area/molecule of about half the molecular cross section, indicating bilayer formation. X-ray fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…Unlike the lanthanide ions where ligands interact electrostatically, transition metals can show significant selectivities due to ligand–metal coordination bonds that are directional. Finally, a paper published while our manuscript was under review confirms the static inverted bilayer structure we propose for the lutetium system …”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Unlike the lanthanide ions where ligands interact electrostatically, transition metals can show significant selectivities due to ligand–metal coordination bonds that are directional. Finally, a paper published while our manuscript was under review confirms the static inverted bilayer structure we propose for the lutetium system …”
Section: Resultssupporting
confidence: 78%
“…Finally, a paper published while our manuscript was under review confirms the static inverted bilayer structure we propose for the lutetium system. 74 The kinetics of monolayer to inverted bilayer transition with Lu 3+ in the subphase is strongly temperature dependent with an activation barrier of ~ 40 kcal/mol. This relatively large energy barrier is in correspondence with the low temperature required to arrest the heavy lanthanide species at the dodecane-water interface.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the type of metal ion and aqueous pH are crucial to maintain a stable DHDP monolayer. 29,33 Here, we found that a low pH value of 2.5 is essential when stabilizing a DHDP monolayer on the surface of aqueous solutions containing Fe(III).…”
Section: Dhdp Monolayer Preparationmentioning
confidence: 83%
“…[17][18][19] Recent studies have used X-ray and neutron scattering and non-linear optical techniques to probe ion-extractant complexes at liquid surfaces and interfaces. 8,[20][21][22][23][24][25][26][27][28][29] Although the importance of complexation in the bulk aqueous solution had been dismissed in earlier work, 17 our recent studies of lanthanide ion complexation with HDEHP in the bulk aqueous phase noted that such complexation can be antagonistic to the intended selectivity of the extraction process. 30 Heavy lanthanides will be held back by HDEHP in the bulk water, which may hinder the extraction efficiency and separation selectivity with light lanthanides.…”
Section: Introductionmentioning
confidence: 99%
“…3 Chemical separations require selective ion adsorption and transfer. [4][5][6][7][8][9][10][11][12][13] A molecular scale understanding of ion-surface-water interactions is crucial for addressing the key challenges in these fields.In the classical picture of a charged interface, including Stern and diffuse layers of electric double layer (EDL), the total charge of the counterions adsorb at the interface cannot exceed the surface charge. However, in the last two decades many experimental and theoretical studies have demonstrated that the charge of adsorbed ions can exceed the surface charge, leading to a charge reversal or overcharging.…”
mentioning
confidence: 99%